INTRODUCING METHODOLOGY TO DETECT DEAD TISSUE STORED ENERGY - Embi, Abraham A. (International Journal of Research -GRANTHAALAYAH, 2022)
The presence of Catalase essential for dead or alive biological tissue energy emission. In a seminal paper describing the origin of magnetic fields in the human body Cohen D. by using sophisticated equipment stated: “Most of the field over the head is produced by electrical sources associated with the hair follicles of the scalp; this field is produced only as a response to touching or pressing the scalp…”. Recently, a tabletop optical microscopy (TTM) method was developed in 2015 and published a year later by Scherlag et al. also enabling detection of electromagnetic fields (EMFs) in plant and animal tissue. That novel microscopy method was achieved in the absence of mechanical instrumentation (as used by Cohen) due to a most interesting property of Potassium Ferricyanide of formula K₃ [Fe (CN)₆ allowing for the total absorption of incoming EMFs. For simplicity, in this manuscript K₃ [Fe (CN)₆ will be replaced by the acronym K3Fe. This manuscript applies TTM methodology able to detect and display EMFs energy emitted from three lizards’ tails; one estimated dead for four weeks, the second and third harvested while alive and used as control. This communication supports a long-standing definition of dead matter “matter composed of organic compounds that has come from the remains of organisms such as plants and animals and their waste products in the environment”. Experiments herein presented support adding the presence of stored remnant energy to the definition. This energy could now be easily displayed even in the absence of life.